Impact of healthy and sustainable diets on the mortality burden from cardiometabolic diseases and colorectal cancer in Mexican adults: a modeling study - Andrea Arango-Angarita; Mishel Unar-Munguía; Rodrigo Zepeda-Tello; Carolina Batis; Juan A. Rivera (BMC Public Health)
Abstract Background Healthy and sustainable diets (HSDs) have been associated with reduced mortality from chronic diseases, particularly in high-income countries. However, evidence from Mexico is limited, and no study has assessed the potential impact on mortality of adopting different HSD scenarios. This study aimed to assess the impact of various HSD scenarios on the mortality burden from cardiometabolic diseases and colorectal cancer (CRC) in Mexican adults. Methods Using a comparative risk assessment model, we examined six HSD scenarios: Mexican Healthy and Sustainable Dietary Guidelines 2023 (MHSDG), EAT-Lancet healthy reference diet (EAT-HRD) and its Mexican adaptation (EAT-HRD-Mx), vegan, vegetarian, and pescatarian diets, compared with the current diet. Disease-related relative risks for food groups were derived from dose-response meta-analyses. The current diet was based on 24-hour dietary recall data from the Mexican National Health and Nutrition Survey (ENSANUT) 2016. HSDs were simulated following intake recommendations for each scenario and the current intake distribution from ENSANUT. Mortality data from type 2 diabetes (T2D), cardiovascular disease (CVD), cerebrovascular disease (CeVD), and CRC were sourced from the 2016 Mexican National Institute of Statistics and Geography (INEGI). Premature deaths were defined as those between 20 and 75 years of age. Years of life lost were estimated by multiplying age-specific deaths by life expectancy. Averted deaths were estimated using potential impact fractions, with 95% uncertainty intervals (UI) derived through bootstrapping. Results Compared with current diets, the HSD scenarios led to reductions in premature (25.1–30.5%) and total (26.6–33.1%) mortality, with greater reductions associated with vegan diets. The MHSDG ranked third with 29·6% of the premature deaths averted (42,470; 95%UI 39,940–45,045) and 31.9% of total deaths (89,337; 95%UI 84,446–94,244). A vegan diet could lead to a major reduction in CVD deaths (62,290; 95%UI 60,271–64,321), whereas pescatarian diets resulted in the highest number of avoided deaths from CeVD (9,791; 95% UI 9,243–10,340). The EAT-HRD was associated with greater reductions in T2D deaths (23,793; 95%UI 21,733–25,859) and CRC (941; 95% UI 838–1,046). Increased consumption of plant-based foods and reduced intake of red meat and sugar-sweetened beverages were the primary contributors to lower mortality rates. Conclusions These findings support the implementation of policies promoting HSDs in Mexico to reduce the burden of cardiometabolic and CRC mortality. Particularly, the MHSDG is a relevant strategy due to its food-system approach, local applicability and cultural alignment.